IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - I Wayan Arsana Ardiantara; I Gede Oka Parmadi; I Ketut Alit Adi Wiratma; I Made Sujana Adnyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the implementation of the Problem Based Learning (PBL) model in improving mathematics learning outcomes of fourth-grade students at SD Negeri 3 Seraya. The study was motivated by low student achievement due to teacher-centered instruction and limited student engagement. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 21 students with varying academic abilities. Data were collected through learning outcome tests (pre-test and post-test), observation sheets of student and teacher activities, and documentation. The data were analyzed using both quantitative and qualitative approaches. The results showed that the implementation of PBL had a positive impact on students’ learning outcomes. The average pre-test score was 62.38 with 38% learning mastery. After the first cycle, the average score increased to 78.57 with 71% mastery. In the second cycle, the average score further improved to 86.19 with 90% mastery. In addition, student activity and engagement also improved, particularly in identifying problems, participating in group discussions, and presenting solutions. In conclusion, the PBL model is effective in improving mathematics learning outcomes and enhancing students’ critical thinking and problem-solving skills. Therefore, PBL is recommended as an innovative teaching strategy to improve the quality of mathematics instruction in elementary schools.